Exploring Instructional Leadership as a Praxis in Schools - Victor J. Pitsoe; Mmalefikane Sylvia Sepeng (Social Sciences and Education Research Review)
The importance of instructional leadership in promoting school growth and renewal is significant; however, it has received limited research attention and is not fully understood. Instructional leadership encompasses the proactive and efficient involvement of principals in initiating, organizing, and executing activities aimed at enhancing curriculum and instruction. Efficient instructional leaders foster teacher collaboration, facilitate professional development, and enhance student achievement. Successfully implementing a change requires overcoming resistance and gaining the support of stakeholders. Through the comprehension and implementation of efficient instructional leadership, educational institutions have the potential to greatly enhance student academic achievement and overall school efficacy.